Pengaruh Model PBL Berbantuan Alat Peraga Kubus Satuan terhadap Kemampuan Numerasi Siswa SD pada Materi Volume Bangun Ruang - Baiq Madina Hasanah; Muhammad Syazali; Muhammad Erfan (Mataram University, 2026)
Previous studies have demonstrated the effectiveness of the Problem-Based Learning (PBL) model and unit cube manipulatives in mathematics instruction. However, studies integrating both approaches to improve elementary school students' numeracy skills in geometry remain limited. This study aimed to examine the effect of the Problem-Based Learning (PBL) model assisted by unit cube manipulatives on the numeracy skills of fifth-grade students in geometry, particularly on the topic of the volume of cubes and rectangular prisms, at SD Negeri 2 Mangkung. This study employed a quantitative approach using a quasi-experimental method with a Nonequivalent Control Group Design. The participants consisted of 29 fifth-grade students selected through the total sampling technique. Data were analyzed using the Shapiro–Wilk normality test, Levene's homogeneity test, Independent Samples t-test, and effect size analysis (Cohen's d). The results revealed that the experimental class achieved a higher mean posttest score (70.00) than the control class (58.57). The hypothesis test produced a significance value of 0.047 (p < 0.05), indicating a significant difference between the two groups. Furthermore, the effect size value of 0.777 indicated a medium practical effect. Therefore, the Problem-Based Learning (PBL) model assisted by unit cube manipulatives significantly improved the numeracy skills of fifth-grade students in geometry.